The Taphonomy of Plant and Livestock Dung Microfossils: An Ethnoarchaeological and Experimental Approach. (4th July 2021) - Portillo, Marta; Dudgeon, Kate; Allistone, Georgia; Raeuf Aziz, Kamal; Matthews, Wendy
ABSTRACT: This study examines the contribution of ethnoarchaeological and experimental research to interdisciplinary approaches on the identification and taphonomy of livestock dung. Ethnographic and experimental records provide comparative reference models on a range of taphonomic issues that are still understudied, such as variation in the type and preservation of plant and faecal microfossils that are excreted with dung and the effects of heating. The focus in the present study is on the taphonomy of ingested phytoliths and calcitic spherulites that originate in the digestive tracts of cattle, sheep and goat found in fresh modern dung pellets. The reported records are from the modern farming village of Bestansur, Iraqi Kurdistan. The experimental results show significant changes in microfossil composition and phytolith and spherulite stability and integrity, with increased melting of phytoliths and variations in morphotype composition (e.g. grass short cells appear less stable) from heating at temperatures around 800°C, whereas the spherulite darkening occurs within a range between 500–700°C, with a maximum production at 650°C. This integrated approach illustrates the contribution of the much-needed ethnographic and experimental records of animal dung to understanding of taphonomic issues, which are fundamental for the interpretation of this valuable microfossil material in archaeology.